1997
DOI: 10.2307/2411045
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Genetics of Ovariole Number in Drosophila melanogaster. I. Segregating Variation and Fitness

Abstract: The number of ovarioles of the Drosophila melanogaster ovary is a trait thought to be associated with female fecundity, and therefore is expected to be under strong natural selection. This hypothesis may be tested by examining patterns of genetic and environmental variation for ovariole number in natural populations, and by determining the association between ovariole number and fitness in isogenic lines derived from a natural population. We measured ovariole number, and competitive fitness and its components,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Intriguingly, EcR heterozygotes and EcR-usp double heterozygotes show a delay in the onset of TF formation (Hodin and Riddiford 1998), a phenotype similar to that observed in this study for D. mauritiana, D. sechellia, and the Honduras strain of D. simulans. Wayne et al (1997) used a quantitative genetic approach to demonstrate substantial genetic variation for ovariole number in D. melanogaster, confirming previous studies (Robertson 1957;Thomas-Orillard 1975;Boulétreau-Merle et al 1982). Interestingly, Wayne and Mackay (1998) found that mutational heritability (V M /V E ) for ovariole number in these lines was low (on the order of 10 Ϫ4 ), suggesting that a relatively small number of loci might contribute to ovariole number differences.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Intriguingly, EcR heterozygotes and EcR-usp double heterozygotes show a delay in the onset of TF formation (Hodin and Riddiford 1998), a phenotype similar to that observed in this study for D. mauritiana, D. sechellia, and the Honduras strain of D. simulans. Wayne et al (1997) used a quantitative genetic approach to demonstrate substantial genetic variation for ovariole number in D. melanogaster, confirming previous studies (Robertson 1957;Thomas-Orillard 1975;Boulétreau-Merle et al 1982). Interestingly, Wayne and Mackay (1998) found that mutational heritability (V M /V E ) for ovariole number in these lines was low (on the order of 10 Ϫ4 ), suggesting that a relatively small number of loci might contribute to ovariole number differences.…”
Section: Discussionsupporting
confidence: 80%
“…Wayne et al (1997) used a quantitative genetic approach to demonstrate substantial genetic variation for ovariole number in D. melanogaster, confirming previous studies (Robertson 1957;Thomas-Orillard 1975;Boulétreau-Merle et al 1982). Interestingly, Wayne and Mackay (1998) found that mutational heritability (V M /V E ) for ovariole number in these lines was low (on the order of 10 Ϫ4 ), suggesting that a relatively small number of loci might contribute to ovariole number differences. In interspecific and interpopulational hybridization experiments, loci on chromosomes 2 and 3, but not on the X chromosome, had substantial effects on ovariole number, both within and between species in the melanogaster species group (Coyne et al 1991;Chakir et al 1995).…”
Section: Discussionsupporting
confidence: 80%
“…This result differed from that found by David (1970) and Bouletreau-Merle et al (1982), who observed a positive correlation between ovariole number and the maximum daily rate of oviposition. The difference between these studies could be based on differences in how female fecundity was measured and further experiments are required to explain the discrepancy (Wayne et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between ovariole number and fitness has not been well established within any Drosophila species. Wayne et al (1997) studied 45 isogenic lines of D. melanogaster derived from nature but found no correlation between ovariole number and fitness. This result differed from that found by David (1970) and Bouletreau-Merle et al (1982), who observed a positive correlation between ovariole number and the maximum daily rate of oviposition.…”
Section: Discussionmentioning
confidence: 99%
“…Some models for mutationally driven extinction focus entirely on such mutations (Lynch and Gabriel 1990;Lande 1994;Lynch et al 1995). Recent studies with Drosophila have shown that the fitness effects of spontaneous mutations are strongly environment dependent and exhibit strong genotype X environment interaction (Kondrashov and Houle 1994;Fry et al 1996;Fernandez and Lopez-FanjuI1997;Wayne and Mackay 1998), although none of these studies has revealed a class of mutations that are clearly deleterious in one environment and beneficial in another.…”
Section: Discussionmentioning
confidence: 99%